Role of new anticoagulants for the prevention of venous thromboembolism after major orthopaedic surgery and in hospitalised acutely ill medical patients - Ageno, Walter; Spyropoulos, Alex C.; Turpie, Alexander G. G. (Thrombosis and Haemostasis, 2012)
Anticoagulation therapy for the prevention of venous thromboembolic events is indicated in patients after major orthopaedic surgery and in hospitalised acutely ill medical patients, who have a high or moderate risk of venous thromboembolism (VTE), respectively. Clinical trials have clearly demonstrated that short-term anticoagulation reduces the risk of VTE in these patient groups and that longer-term anticoagulation is beneficial for some indications. Evidence-based guidelines for throm-boprophylaxis have been developed based on these studies. However, despite these guidelines, thromboprophylaxis is still underused, or used suboptimally, in many patients. This is, in part, because of the limitations of traditional anticoagulants such as unfractionated heparin, lowmolecular-weight heparin, synthetic pentasaccharides, and vitamin K antagonists. Newer oral anticoagulants, such as rivaroxaban, apixaban, and dabigatran etexilate, have certain advantages over traditional agents. They can be administered orally at a fixed dose without routine coagulation monitoring and have minimal food and drug interactions. These characteristics may result in better adherence to guidelines and improved patient outcomes. This review provides an overview of phase III clinical trial data for these newer anticoagulants in major orthopaedic surgery and in hospitalised acutely ill medical patients, and discusses their potential for extended use in the post-hospital discharge setting. All three newer oral anticoagulants are approved in many countries for the prevention of VTE after hip replacement or knee replacement surgery in adult patients, and it is likely that these drugs will contribute considerably towards reducing the substantial healthcare burden associated with VTE.
Keywords: Apixaban; dabigatran etexilate; medically ill; orthopaedics; rivaroxaban